On Some Interpolative Contractions of Suzuki Type Mappings. (23rd July 2021) - Fulga, Andreea; Yeşilkaya, Seher Sultan
Abstract : The goal of this study is to propose a new interpolative contraction mapping by using an interpolative approach in the setting of complete metric spaces. We present some fixed point theorems for interpolative contraction operators using w -admissible maps which satisfy Suzuki type mappings. In addition, some results are given. These results generalize several new results present in the literature. Moreover, examples are provided to show the suitability of our given results.